2016
DOI: 10.1111/gcb.13456
|View full text |Cite
|
Sign up to set email alerts
|

Barren‐ground caribou (Rangifer tarandus groenlandicus) behaviour after recent fire events; integrating caribou telemetry data with Landsat fire detection techniques

Abstract: Fire regimes are changing throughout the North American boreal forest in complex ways. Fire is also a major factor governing access to high‐quality forage such as terricholous lichens for barren‐ground caribou (Rangifer tarandus groenlandicus). Additionally, fire alters forest structure which can affect barren‐ground caribou's ability to navigate in a landscape. Here, we characterize how the size and severity of fires are changing across five barren‐ground caribou herd ranges in the Northwest Territories and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
(106 reference statements)
1
22
0
Order By: Relevance
“…Caribou tend to select mature stands (>40 years old) containing relatively abundant lichen cover (Joly et al 2003) and avoid immature stands, although recent studies have found that there may be more individual variation in the use of these areas than previously thought (Anderson and Johnson 2014), and some individuals may take advantage of these areas for increased vascular forage (Joly et al 2003). Caribou may also use immature stands as habitat for movement (Rickbeil et al 2016) or possibly to reduce predation risk through enhanced visibility (Anderson and Johnson 2014). The effects of fire on caribou winter habitat, and associated avoidance by individuals, extend well beyond the short-term loss of vegetation due to the recovery time of lichen species.…”
Section: Winter Range Conditionsmentioning
confidence: 99%
“…Caribou tend to select mature stands (>40 years old) containing relatively abundant lichen cover (Joly et al 2003) and avoid immature stands, although recent studies have found that there may be more individual variation in the use of these areas than previously thought (Anderson and Johnson 2014), and some individuals may take advantage of these areas for increased vascular forage (Joly et al 2003). Caribou may also use immature stands as habitat for movement (Rickbeil et al 2016) or possibly to reduce predation risk through enhanced visibility (Anderson and Johnson 2014). The effects of fire on caribou winter habitat, and associated avoidance by individuals, extend well beyond the short-term loss of vegetation due to the recovery time of lichen species.…”
Section: Winter Range Conditionsmentioning
confidence: 99%
“…For example existing datasets on barren ground caribou ( Rangifer tarandus groenlandicus ) could provide samples from tundra and grasslands (Rickbeil et al. , ), greylag geese ( Anser anser ) could inform us on the existence of permanent – and temporary – water bodies (Kleinhenz and Koenig ), and forest elephants ( Loxodonta cyclotis ) could inform us on both grasslands and forests (Mills et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this paper focuses on agriculture, the potential of movement data to map land cover is far reaching. For example existing datasets on barren ground caribou (Rangifer tarandus groenlandicus) could provide samples from tundra and grasslands (Rickbeil et al 2017(Rickbeil et al , 2018, greylag geese (Anser anser) could inform us on the existence of permanentand temporarywater bodies (Kleinhenz and Koenig 2018), and forest elephants (Loxodonta cyclotis) could inform us on both grasslands and forests (Mills et al 2018). To achieve this, we encourage research on the environmental requirements of different species and on the link between these requirements and concrete land cover types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, if habitat changes are to be documented, repeat measures of habitat conditions over time are required. These challenges are encouraging the development of novel methods for tracking habitat conditions in the north that involve using ex situ data such as space-borne remote sensing (Falldorf, Strand, Panzacchi, & Tømmervik, 2014;Rickbeil, Coops, & Adamczewski, 2015;Rickbeil, Hermosilla, Coops, White, & Wulder, 2016). There are multiple remote sensing platforms and sensors that can be employed for habitat change analysis.…”
Section: Introductionmentioning
confidence: 99%